Experience of Using Hyperbaric Oxygenation in the Treatment of Radionecrosis That Developed as a Complication of Stereotactic Radiosurgical Treatment of Meningioma on the Example of a Clinical Case - A. S. Tokarev; V. N. Stepanov; V. A. Rak; O. L. Yevdokimova; I. A. Terekhin; M. V. Neznanova; O. A. Levina (Неотложная медицинская помощь, 2021)
In contrast to conventional microsurgery, stereotactic radiosurgery has an advantage in the treatment of intracranial masses, avoiding severe complications associated with open surgery. In rare cases, the use of the method is associated with the development of radiation-induced injuries, one of which is radiation necrosis (RN). This is a late complication of radiosurgery, developing mainly 6 months after radiation exposure. The neurological manifestations of this complication depend on location, and the clinical picture is very diverse. The method of magnetic resonance imaging (MRI) with intravenous contrast enhancement is quite often the first link in neuroimaging, which helps to suggest the presence of this complication based on the X-ray picture and to clarify the location of changes.We presented the experience of radiation necrosis treatment in a 47-year-old patient who was referred to our department with a diagnosis of frontal meningioma. The patient underwent stereotactic radiosurgical treatment using the Elekta Leksell Gamma Knife Perfextion device, and 6 months later the gradual deterioration began, the patient complained of headache, nausea; central prosoparesis developed. Considering the clinical picture and control MRI data, the changes were interpreted as radionecrosis. In order to control the complication, the patient underwent standard glucocroticosteroid therapy, supplemented by hyperbaric oxygenation (HBO), which made it possible to achieve regression of the adverse clinical and radiological manifestations of the complication. Thus, on a clinical example, it was demonstrated that the combined use of glucocorticosteroids and HBOs is highly effective in the treatment of RN.